2013
DOI: 10.1002/term.1654
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring nutrient transport in tissue-engineered grafts

Abstract: Limited nutrient diffusion in three-dimensional (3D) constructs is a major concern in tissue engineering. Therefore, monitoring nutrient availability and diffusion within a scaffold is an important asset. Since nutrients come in various forms, we have investigated the diffusion of the oxygen, luciferin and dextran molecules within tissue-engineered constructs using optical imaging technologies. First, oxygen availability and diffusion were investigated, using transgenic cell lines in which a hypoxia-responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…7,10 Earlier studies have established that BLI signal is dependent on variables, including construct composition, luciferin delivery method, animal model, sample positioning, and progression of tissue development in vivo. 6,10,12 Our work draws attention to the impact of tissue and vascular ingrowth on the accuracy of longitudinal BLI measurement. As BLI is frequently used to visualize systems containing a dynamic vascular network, we believe this validation is critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10 Earlier studies have established that BLI signal is dependent on variables, including construct composition, luciferin delivery method, animal model, sample positioning, and progression of tissue development in vivo. 6,10,12 Our work draws attention to the impact of tissue and vascular ingrowth on the accuracy of longitudinal BLI measurement. As BLI is frequently used to visualize systems containing a dynamic vascular network, we believe this validation is critical.…”
Section: Discussionmentioning
confidence: 99%
“…1,11 In 3D cell culture systems, BLI signal is affected by a range of additional variables such as luciferin transport kinetics and light scattering properties of the construct. 10,12 BLI measured from cells seeded within constructs of significantly different material properties has been found to differ in magnitude, but to be linearly correlated to Luc content when evaluated in vitro. 13 Given the complexity of the 3D system in vitro, this evaluation becomes even more complicated when the 3D construct is implanted.…”
Section: Introductionmentioning
confidence: 97%
“…258 When cells are subjected to low oxygen conditions (hypoxia), numerous genes are up-or down-regulated, like angiogenesis related genes to promote cell survival. 259 To study this, a CHO cell line (CHO HRE-GFP cells) transfected with a green fluorescence protein (GFP) hypoxia reporter, was employed to demonstrate the ability of our microfluidic platform to recapitulate normal and hypoxia conditions. The cells fluoresce in case of limited availability of oxygen.…”
Section: Hypoxia Assaymentioning
confidence: 99%
“…More specifically, hypoxia-inducible factor-1 (HIF-1) translocates into the nucleus and binds to the hypoxia responsive element (HRE) promoter, thereby activating GFP transcription (for details on transfection and clonal procedure, please see the earlier work by Liu and co-workers). 259 CHO cells were cultured in the chip, under normal and reduced oxygen conditions inside the chip holder, using regular culture medium supplied at a flow rate of 1 µL·h -1 through the supply channels. Under these conditions, the residence time of 6 h, was sufficient for the medium to reach equilibrium through the PFA tubing.…”
Section: Hypoxia Assaymentioning
confidence: 99%
“…The principle has proven useful to monitor gene expression and cellular activities both in vitro and in small animal models in vivo [164][165][166]. Several studies have shown the correlation between luciferase activity and the number of cells within tissues in vivo or scaffolds in vitro.…”
Section: Bioluminescence(bli)mentioning
confidence: 99%